2019
DOI: 10.1016/j.neuroimage.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Passive exposure to speech sounds modifies change detection brain responses in adults

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Moreover, studies with monolinguals have also shown that shorter-term foreign language learning impacts other cognitive processes in monolingual adults [ 26 ] and children [ 25 ]. In addition to the impact of foreign language learning, passive language exposure can also impact other cognitive processes, as shown in the studies by Bice and Kroll [ 21 ] or Kurkela et al [ 23 ]. These studies show that even short-term language exposure leaves traces that cannot be easily ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies with monolinguals have also shown that shorter-term foreign language learning impacts other cognitive processes in monolingual adults [ 26 ] and children [ 25 ]. In addition to the impact of foreign language learning, passive language exposure can also impact other cognitive processes, as shown in the studies by Bice and Kroll [ 21 ] or Kurkela et al [ 23 ]. These studies show that even short-term language exposure leaves traces that cannot be easily ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with monolinguals have found that short-term foreign language exposure as well as foreign language learning influence both language processing (e.g., [ 21 24 ]) and executive control in monolingual children [ 25 ] and monolingual adults [ 26 ]. For example, Kurkela et al [ 23 ] found that adult Finnish monolinguals who were passively exposed to Mandarin speech sounds for four days showed greater neural discrimination to novel verbal and nonverbal auditory stimuli. Furthermore, Bice and Kroll [ 21 ] discovered that monolinguals immersed in linguistically diverse environments seemed to develop higher sensitivity to non-native phonological contrasts when learning words in a new language.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies with monolinguals have also shown that shorter-term foreign language learning impacts other cognitive processes in monolingual adults [25] and children [24]. In addition to the impact of foreign language learning, passive language exposure can also impact other cognitive processes, as shown in the studies by Bice and Kroll [20] or Kurkela et al [22]. These studies show that even short-term language exposure leaves traces that cannot be easily ignored.…”
Section: The Impact Of Heterogeneous Language Experience On Bilinguals' and Monolinguals' Cognitionmentioning
confidence: 93%
“…Studies with monolinguals have found that short-term foreign language exposure as well as foreign language learning influence both language processing (e.g., [20][21][22][23]) and executive control in monolingual children [24] and monolingual adults [25]. For example, Kurkela et al [22] found that adult Finish monolinguals who were passively exposed to Mandarin speech sounds for four days showed greater neural discrimination to novel verbal and nonverbal auditory stimuli. Furthermore, Bice and Kroll [20] discovered that monolinguals immersed in linguistically diverse environments seemed to develop higher sensitivity to nonnative phonological contrasts while learning words in a new language.…”
Section: Monolingual Language Experience and Its Impact On Language And Cognitionmentioning
confidence: 99%
See 1 more Smart Citation